2021
DOI: 10.18203/2320-6012.ijrms20214413
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of neutropenic fever and sepsis in patients receiving induction chemotherapy in acute leukemia

Abstract: Background: Acute leukemias are treated with intensive chemotherapy protocols which are associated with increased risk of infections. The objective of this study was to determine the incidence of febrile neutropenia and sepsis in acute leukemia patients during induction chemotherapy.Methods: In this prospective study we analysed the data of febrile neutropenia of forty-four patients of acute leukemia treated with intensive chemotherapy protocols. Study was conducted in hemato-oncology unit of Government Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…These infections lead to adverse outcomes during the intense phase of treatment and exacerbate mortality [ 7 ]. Despite the existence of comprehensive guidelines for supportive care and management of infections, complicated febrile neutropenia remains the most prevalent cause of mortality during inducting chemotherapy in acute leukemia patients, and the results of our study are suggestive of this finding [ 8 ].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…These infections lead to adverse outcomes during the intense phase of treatment and exacerbate mortality [ 7 ]. Despite the existence of comprehensive guidelines for supportive care and management of infections, complicated febrile neutropenia remains the most prevalent cause of mortality during inducting chemotherapy in acute leukemia patients, and the results of our study are suggestive of this finding [ 8 ].…”
Section: Discussionmentioning
confidence: 71%
“…Febrile neutropenia is a life-threatening oncological emergency that emphasizes the need for comprehensive research and improved therapeutic strategies to address the challenges faced by patients undergoing induction chemotherapy [ 8 , 9 ]. A developing nation such as Pakistan grapples with the complexities of the management of febrile neutropenia, where limited resources and access to advanced medical care add a layer of adversity [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study states, sepsis occurred in 76.6% patients (46/60). In an Indian study, Prasoon et al, (2021) reported the 20% incidence of sepsis in case of ALL during induction chemotherapy 9. In this study, the comparison of serum IgG and IgA levels between the control group and the study population showed that the mean IgG during baselineIgA level (…”
mentioning
confidence: 53%